Aerosol optical depth retrievals in central Amazonia from a multi-filter rotating shadow-band radiometer calibrated on-site - Rosario, Nilton E.; Sauini, Thamara; Pauliquevis, Theotonio; Barbosa, Henrique M. J.; Yamasoe, Marcia A.; Barja Gonzalez, Boris (My University, 2019)
Extraterrestrial spectral response calibration of a multi-filter rotating shadow band radiometer (MFRSR) under pristine Amazonian Forest atmosphere conditions was performed using the Langley plot method. The MFRSR is installed in central Amazonia as part of a long-term monitoring site, which was used in the context of the GoAmazon2014/5 experiment. It has been operating continuously since 2011 without regular extraterrestrial calibration, preventing its application to accurate monitoring of aerosol particles. Once calibrated, the MFRSR measurements were applied to retrieve aerosol particle columnar optical properties, specifically aerosol optical depth (AOD(lambda)) and Angstrom exponent (AE), which were evaluated against retrievals from a collocated Cimel Sun photometer belonging to the AErosol RObotic NETwork (AERONET). Results obtained revealed that pristine Amazonian conditions are able to provide MFRSR extraterrestrial spectral response with relative uncertainty lower than 1.0% in visible channels. The worst estimate (air mass = 1) for absolute uncertainty in AOD(lambda) retrieval varied from approximate to 0.02 to approximate to 0.03, depending on the assumption regarding uncertainty for MFRSR direct normal irradiance measured at the surface. The obtained root mean square error (RMSE approximate to 0.025) from the evaluation of MFRSR retrievals against AERONET AOD(lambda) was, in general, lower than estimated MFRSR AOD(lambda) uncertainty, and close to the uncertainty of AERONET field Sun photometers (approximate to 0.02).
Keywords: AERONET; Sun photometer; Photometer